A comparison of diverticulitis in Crohn's disease versus ulcerative colitis. Issue 6 (7th May 2019) - Persaud, Alana; Ahmed, Ahmed; Kakked, Gaurav; Shulik, Oleg; Ahlawat, Sushil
Abstract : Background and Aim: Inflammatory bowel disease (IBD) and diverticulitis both increase morbidity, especially when associated with in‐patient hospitalization. This study aimed to evaluate whether hospitalization burden differs for diverticulitis in patients with a history of Crohn's disease (CD) compared to ulcerative colitis (UC). Method: All patients hospitalized for acute diverticulitis with pre‐existing UC or CD in 2014 were selected using the national in‐patient sample. Cases were identified using the International Classification of Diseases, Ninth Edition codes. Primary outcomes were mortality, cost of admission, length of stay (LOS), and colectomy. Results: A total of 1815 patients were admitted with diverticulitis, and those with CD had a hospitalization associated with decreased cost (aOR −14 537, 95% CI −27 316 to −1758; P = 0.026) and LOS (aOR −1.31, 95% CI −2.41 to −0.208; P = 0.02) compared to UC. A second analysis comparing diverticulitis hospitalization between those with CD and those with the absence of IBD showed no significant difference in mortality (aOR 2.47, 95% CI 0.59 to 10.36; P = 0.22), LOS (aOR 0.03, 95% CI −0.47 to 0.54; P = 0.92), or cost of admission (aOR −2196, 95% CI −6933 to 2539; P = 0.36) between the cohorts. Conclusion: Patients with UC have worsened hospitalization outcomes when being treated for diverticulitis compared to CD. While the findings may be a result of a difference in colectomy rates, the etiology may also be multifactorial. These conclusions have not been previously described, and further investigations would better characterize these associations. Abstract : Inflammatory bowel disease is quite prevalent, but it is unknown whether concurrent diverticulitis affects ulcerative colitis (UC) and Crohn's disease in different ways. The national in‐patient sample in 2014 demonstrated that diverticulitis with simultaneous UC resulted in increased mortality, cost of hospitalization, and length of stay compared to Crohn's disease. While colectomies may account for these findings, the cause is likely multifactorial, and these data indicate the population that may require more medical resources when hospitalized for acute diverticulitis.